PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS X SEMESTER GENAP SMA NEGERI 2 GADING REJO TAHUN PELAJARAN 2015/2016 - Zainal, Vetri Yanti (Lentera: Jurnal Ilmiah Kependidikan, 2018)
The aim of this research is for knowing the influence of applying Problem Based Learning towards the students‟ learning result at the even semester of the tenth class of SMA Negeri 2 Gading Rejo academic year 2015/2016. In this research, researcher used experimental method. The population were 156 students. The sample in this research were 2 classes. Class X2 was experimental class which consisted of 34 studentstaugh using problem based learning model, and Class X6 was control class which consisted of 34 students taugh using conventional model. Cluster random sampling was used as sampling technique. t-test formula was used in testing the hypothesis. The analysis resulted that thit = 6,39 and after consulted to t table with 5% significance level, it got ttab = 1,98. Therefore, it was proved that thit>ttab. It meant that Ho was rejected. It can be concluded that there is an influence of applying Problem Based Learning towards the students‟ learning result at the tenth class of SMA Negeri 2 Gading Rejo academic year 2015/2016.